Validity and reliability of the Malay translated version of the diabetes health literacy scale among Malaysian adults with type 2 diabetes mellitus - Ling, Ng Pei (2024)
Introduction: The instrument for measuring health literacy among Malaysian adults with type 2 diabetes mellitus (T2DM) is limited. A valid and reliable diabetes-specific health literacy instrument in Malay is required before it can be used in measuring diabetes health literacy and determining its relationship with other variables. Objective: The aim of this study was to determine the validity and reliability of the Malay version of the Diabetes Health Literacy Scale (DHLS-M) among Malaysian adults with T2DM. Method: The Diabetes Health Literacy Scale (DHLS) was translated and culturally adapted into Malay, followed by a cross-sectional study which was conducted using a self-administered questionnaire among the adults with T2DM in Hospital Universiti Sains Malaysia (USM). The participants were recruited by convenience sampling. Confirmatory factor analysis (CFA), reliability testing and correlation analysis were performed. Results: A total of 250 adults with T2DM were participated in this study. The median age of the participants was 63.0 years old (interquartile range, IQR = 12.3) and most of the participants were male (51.2%). The final measurement model of DHLS-M with removal of one problematic item, fit the data well based on several fit indices: Relative chi-square (χ2/df) = 3.858, comparative fit index (CFI) = 0.981, Tucker–Lewis index (TLI) = 0.976. The composite reliability of the three subscales based on Raykov's rho were 0.962, 0.836 and 0.828 respectively. The subscales of DHLS-M were significantly correlated with the Malay version of the Michigan Diabetes Knowledge Test (MDKT) (r = 0.26 – 0.31) and the Malay version of the short form Health Literacy Survey Questionnaire (HLS-SF12) (r = 0.43 – 0.66). Conclusion: DHLS-M which consisted of three subscales and 13 items is valid and reliable. DHLS-M can be used to measure diabetes health literacy among Malaysian adults with T2DM.